Alveolar Bone Loss Analysis on Dental Digital Radiography Image - Fitriananda, Aulia Karina; Kiswanjaya, Bramma; Bachtiar-Iskandar, Hanna H (UI Scholars Hub, 2021)
Background: Periodontal disease is the second most common tooth and mouth disease in Indonesia. Moreover, radiographic examination is the most useful tool to evaluate alveolar bone loss and diagnose periodontal diseases. This study aimed to analyze radiographically the relationship between alveolar bone loss and age among patients with chronic periodontitis. Methods: A total of 192 digital periapical images of patients aged 25–40 years were collected. Four regions were selected, including the maxillary and mandibular central incisors and maxillary and mandibular first molars. Alveolar bone loss was measured in the mesial and distal surfaces. Results: The mean and standard deviation for alveolar bone loss in age categories 1 (age 25–32 years) and 2 (age 33–40 years) were 4.03 ± 1.46 and 5.23 ± 2.5 (mm), respectively. Alveolar bone loss demonstrated a significant relationship with patient’s age (p < 0.001, Mann–Whitney U test). Conclusions: The mean and standard deviation of alveolar bone loss reduction in patients with chronic periodontitis was 4.87 ± 0.2 (mm). The alveolar bone loss on the mandibular central incisors’ mesial surface is the highest among other regions.